Dendritic cell tumor in a salivary gland lymph node: a rare differential diagnosis of salivary gland neoplasms - Wolburg Hartwig; Fend Falko; Syha Roland; Plontke Stefan K; Schraven Sebastian P; Adam Patrick (BMC, 2011)
Abstract Dendritic cell tumors are extremely rare neoplasms arising from antigen-presenting cells of the immune system. We report a case of a 69-year-old man with an unremarkable medical history who presented with a 2-months history of a gradually enlarging painless, firm, mobile, 2 × 2-cm swelling at the caudal pole of the left parotid gland without systemic symptoms. Histologically, the tumor consisted of a spindle cell proliferation in an intraparotideal lymph node. Based on the histopathologic, immunohistochemical and electron microscopic findings, a dendritic cell tumor, not otherwise specified (NOS) in an intraparotideal lymph node was diagnosed. The patient underwent complete tumor resection, and is currently free of disease, 2 years after surgery. These extremely rare tumors must be distinguished from other more common tumors in the salivary glands. Awareness that dendritic cell tumors may occur in this localization, careful histologic evaluation and ancillary immunohistochemical and electron microscopical analyses should allow for recognition of this entity.